Face Recognition Using Hybrid Algorithm - Jindal, Balkrishan; Singh, Tarsem (International Journal of Computer Sciences and Engineering, 2025)
In this paper Genetic and Fuzzy hybrid approach is used to recognize the face from the data set to improve the reorganization rate. The proposed method is implements in a four steps. Any sensor device is used to sense the face attributes and measured the attributes used for biometrics based identity. In second step any collected data from the sensor device will be pre-processed. Various types of noises in the attribute will be removed for increasing the accuracy for post processing. In the third step various features required for matching will be extracted. These features are identified from the inputted image. In fourth step these collected features values are stored into the database as training set. Later on any input image attribute values are matched with the stored dataset features. Whom the features will be matched will return success else will return failure.